Case Report: A novel LHFPL3::NTRK2 fusion in dysembryoplastic neuroepithelial tumor - Chen, Yanming; Zhu, Qing; Wang, Ye; Dai, Xiaoxiao; Chen, Ping; Chen, Ailin; Zhou, Sujuan; Dai, Chungang; Zhao, Shengbin; Xiao, Sheng; Lan, Qing (Frontiers in Oncology, 2022)
Neurotrophic tyrosine receptor kinase (NTRK) rearrangements are oncogenic drivers of various types of adult and pediatric tumors, including gliomas. However, NTRK rearrangements are extremely rare in glioneuronal tumors. Here, we report a novel NTRK2 rearrangement in a 24-year-old female with dysembryoplastic neuroepithelial tumor (DNT), a circumscribed WHO grade I benign tumor associated with epilepsy. By utilizing targeted RNA next-generation sequencing (NGS), fluorescence in situ hybridization (FISH), reverse transcriptase PCR (RT-PCR), and Sanger sequencing, we verified an in-frame fusion between NTRK2 and the lipoma HMGIC fusion partner-like 3 (LHFPL3). This oncogenic gene rearrangement involves 5’ LHFPL3 and 3’ NTRK2, retaining the entire tyrosine kinase domain of NTRK2 genes. Moreover, the targeted DNA NGS analysis revealed an IDH1 (p.R132H) mutation, a surprising finding in this type of tumor. The pathogenic mechanism of the LHFPL3::NTRK2 in this case likely involves aberrant dimerization and constitutive activation of RTK signaling pathways.